Intervensi Nonfarmakologi terhadap Nausea dan Vomiting pada Pasien Kanker dengan Kemoterapi - Anis Isnaeniyah; Allenidekania Allenidekania (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to review various studies related to non-pharmacological interventions that can reduce or overcome CINV in cancer patients. The method used in this research was a literature search conducted on the PubMed, Ebsco, ProQuest, and Google Scholar databases. The research results obtained ten articles that met the inclusion criteria. From the literature review, eight interventions were obtained that can be used to reduce or overcome CINV. In conclusion, non-pharmacological interventions that can be given to cancer patients who experience CINV are peppermint essential oil aromatherapy, nutritional counseling, acupuncture, music therapy combined with other treatments, foot massage, foot reflexology, behavioral intervention, and breathing exercises. Keywords: Chemotherapy, Intervention, Nausea, Vomiting